SISTEM INFORMASI RAWAT INAP KLIEN DI BRSKP NAPZA â€SATRIAâ€ BATURRADEN BERBASIS WEBSITE - Wijianto, Ragil; Maarif, Vadlya; Ariesta, Lina (APMMI - Asosiasi Profesi Multimedia Indonwsia, 2020)
Abstract - In the current era of globalization, the development of technology and information is so fast. This progress has a good impact on society because it can facilitate the work in terms of speed and access to information. The Social Rehabilitation Center for the